Analysis of mathematical concept comprehension ability in slow learners students - Sopia, Fasya Fi'la; Balkist, Pujia Siti; Nurcahyono, Novi Andri (Universitas Sarjanawiyata Tamansiswa, 2024)
Mathematical comprehension is a fundamental skill that plays a crucial role in understanding and solving problems across various mathematical topics. This study aims to analyze the mathematical comprehension abilities of slow learners in the SPLDV (Two-Variable Linear Equation System) material. A descriptive qualitative approach was employed in this study. The subjects consisted of 20 slow learners in grade VIII of SMPIT in Sukabumi Regency. Data were collected through written tests and interviews, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that students with low comprehension skills have not fully mastered the SPLDV material and can only answer questions at levels 1, 2, and 3 but do not fully meet the indicators. Students with medium comprehension skills are able to answer questions at levels 1 and 2 according to the indicators. Meanwhile, students with high comprehension skills can answer questions at levels 1, 2, and 3 while meeting the indicators. The analysis of answers and interview data reveals that students in the low, medium, and high comprehension categories demonstrate distinct indicators of mathematical comprehension ability. In conclusion, slow learners exhibit varied levels of mathematical comprehension, highlighting the need for differentiated teaching strategies to address their specific needs and enhance their understanding of SPLDV concepts.